The role of transformational leadership in professional learning communities: Empirical evidence from China - Lei Gao; Aida H. A. Hamid; Azlin N. Mansor (Journal of Pedagogical Research, 2024)
Few existing research examines the relationship between transformational leadership and professional learning communities. This study aims to explore the relationship between transformational leadership and professional learning community components from the perspective of teachers in the Chinese context. A total of 385 primary school teachers participated in the questionnaire survey. This quantitative study used the 12-item Multifactor Leadership Questionnaire and the16-item PLC scale. The structural equation model showed a good fit. The results showed that transformational leadership had a significant positive effect on professional learning community. Moreover, it has a significant impact on all four components of PLC, namely, organizational learning, shared responsibility, reflective dialogue, de-privatized practice. Transformational leadership conflicts with Chinese Confucian culture on some core features, which provides valuable cases for research on the applicability of transformational leadership in different contexts. At the same time, it also provides empirical evidence for the study of the relationship between transformational leadership and professional learning communities.